Graphene-Modified Titanium Surface Enhances Local Growth Factor Adsorption and Promotes Osteogenic Differentiation of Bone Marrow Stromal Cells - Lu, Jiayu; Sun, Jiayue; Zou, Derong; Song, Jinlin; Yang, Sheng (Frontiers in Bioengineering and Biotechnology, 2021)
Graphene coating exhibits excellent abilities of protein adsorption and cell adhesion, which might expand the osteogenic activity of titanium implant surface to adapt to the environment of low bone mass and poor bone quality. In this paper, we designed and explored the graphene-coated titanium sheet, through the surface modification of oxygen-containing functional groups, to optimize the adsorption capacity of material by improving the electrostatic interactions, and successfully adsorbed and sustained-released a variety of osteogenic related growth factors in the autologous concentrated growth factors. Compared with the pure titanium, we observed that the bone marrow stromal cells (BMSCs) on the graphene-coated titanium with concentrated growth factors showed a flat shape and expressed osteogenic related genes and proteins, while the coating surfaces promoted and accelerated the osteogenic differentiation ability of BMSCs. The results suggested that it might be a feasible alternative to improve the osteogenesis of dental implants in the early stage.